2011
DOI: 10.1002/apj.453
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and catalytic performance of SAPO‐34 molecular sieves for methanol‐to‐olefin (MTO) reaction

Abstract: The methanol-to-olefin (MTO) process is important because it offers an alternative to the conventional oil route for the conversion of natural gas or coal to light olefins. The most promising catalysts for the MTO reaction are solid acids with a zeolite structure, where reactants and products such as ethylene and propylene may freely diffuse through active catalysts, but products with larger kinetic diameters are trapped within the cages. In this work, SAPO-34 molecular sieves were synthesized by hydrothermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Because the particle aggregation takes place rapidly after nucleation, controlling the appropriate crystallization time is the most important factor in obtaining SAPO-34 with small crystals. Also, as a result of high crystallinity at longer crystallization span, the surface area is significantly increased and this result is in agreement with the data obtained by other researchers which showed that the surface area increases gradually with enhancing the crystallinity of SAPO-34 [34].…”
Section: Crystallization Timesupporting
confidence: 92%
See 2 more Smart Citations
“…Because the particle aggregation takes place rapidly after nucleation, controlling the appropriate crystallization time is the most important factor in obtaining SAPO-34 with small crystals. Also, as a result of high crystallinity at longer crystallization span, the surface area is significantly increased and this result is in agreement with the data obtained by other researchers which showed that the surface area increases gradually with enhancing the crystallinity of SAPO-34 [34].…”
Section: Crystallization Timesupporting
confidence: 92%
“…There are various works which studied effects of crystallization time [32][33][34][35][36][37][38]. They confirm that with increasing crystallization period, crystals grow larger.…”
Section: Crystallization Timementioning
confidence: 99%
See 1 more Smart Citation
“…However, the MTO process is profitable only when the price of petroleum is high. To maximize the chemical reaction conversion, several industrial catalysts have been investigated …”
Section: Introductionmentioning
confidence: 99%
“…Hydrothermal method, as the conventional strategy, has been applied in the preparation of SAPO-34 by numerous researchers [4][5][6][7][8][9][10][11][12][13][14][15]. However, separation between solvents and solid products is required by filtration or centrifugation, and partial organic SDAs are inevitably preserved in the liquid phase, resulting in the wastewater pollutants and downstream purification system installation [16].…”
Section: Introductionmentioning
confidence: 99%